On the Investigation of a Novel Dual-Control-Gate Floating Gate Transistor for VCO Applications - Abderrezak Marzaki; V. Bidal; R. Laffont; W. Rahajandraibe; J-M. Portal; E. Bergeret; R. Bouchakour (Bulletin of Electrical Engineering and Informatics, 2013)
A new MOS device called Dual-Control Gate Floating Gate Transistor (DCG-FGT) is used as a building block in analog design. This device offers new approaches in circuit design and allows developing new functionalities through two operating modes: Threshold Voltage Adjustable Mode, where the DCG-FGT behaves like a MOS transistor with an electrically adjustable threshold voltage. Mixer Signal Mode where the DCG-FGT can mix two independent signals on its floating gate. This device is developed to be fully compliant with CMOS Non Volatile Memory (NVM) process. An electrical model of the DCG-FGT has been implemented in an electrical simulator to be available for analog design. A DCG-FGT based ring oscillator is studied in this paper.